Peculiarities in difficult walking of children with progressing neuromuscular diseases (a review of literature) - Chernyshova, Irina; Shevchenko, Stanislav (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
Progressive neuromuscular diseases and orthopaedic pathology are two components of one irreversible process. Analysing scientific literature material, the authors draw a conclusion about the uniformity of the locomotor system affection in the whole variety of forms of progressive neuromuscular diseases, which results in loss of the ability to retain the vertical posture and move owing to a primary or secondary dystrophic lesion of the muscular and connective tissue.